PENGARUH PAD DAN DAU TERHADAP BELANJA MODAL DI KABUPATEN HULU SUNGAI SELATAN - ZAINAL ILMI; MUHAMMAD SALEH (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The purpose in this research is to know effect partially and simultaneously of PAD and DAU to BM in Hulu Sungai Selatan regency. The data research from DJPK Kemenkeu RI which the data research is LRA APBD of Hulu Sungai Selatan regency 2003-2017 and type data of research is time series data, then technical analysis used multiple linear regression analysis. The result of research showed PAD has negative and not significant effect to BM in Hulu Sungai Selatan Regency 2003-2017, DAU has positive and significant effect to BM in Hulu Sungai Selatan Regency 2003-2017, then by simultaneously or together, PAD and DAU have significant effect to capital expenditure in Hulu Sungai Selatan Regency 2003-2017.